ME-FINE: Mannheim European panel on Financial Indicators and Emissions - Robert Germeshausen; Bettina Chlond; Kinga Tchorzewska; Kathrine von Graevenitz (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
The Mannheim European panel on Financial Indicators and Emissions (ME-FINE) is a new European company-level dataset, combining financial information from Bureau van Dijk's Orbis database with data on pollutant emissions from the European Pollutant Emission Register (EPER) and its successor, the European Pollutant Release and Transfer Register (E-PRTR). The current version of ME-FINE spans from 1998 to 2016 and focuses on companies in the manufacturing and energy supply sectors in the EU-15 plus Hungary and Norway. The dataset covers around 70 percent of observations in EPER and E-PRTR in those sectors and countries, representing about more than half of the emissions of the most common (air) pollutants. [...]
Keywords: 330